EFFECT OF LONG TERM SUPPLEMENTATION WITH DIETARY LIPIDS ON GROWTH, FATTY ACID COMPOSITION AND HISTOPATHOLOGY IN RABBITS LIVER - D. M. Al Nouri; S. Arzoo; S. Husain (Journal of Animal and Plant Sciences, 2016)
The purpose of this study was to investigate the effect of long-term supplementation with dietary lipids on growth, fatty acid composition and histopathology of male and female rabbit’s liver. Soybean oil (SBO), fish oil (FO), sesame oil (SO), docosahexaenoic acid (DHA) and docosahexaenoic acid (DHA) / arachidonic acid (ARA) were used as source of dietary lipids (treatments) in this study. The experimental diets were prepared by adding the oil blend to the basal diet (70 g/kg diet). The experiment was conducted on forty-five weanling (25 male (5 in each treatment) and 20 female (4 in each treatment)) New Zealand white rabbits. Dietary lipids had a distinct effect on growth rate particularly in males. Male rabbits fed the fish oil diet showed the highest total omega-3 (ω-3) fatty acids, lowest ω-6/ω-3 and ARA/EPA ratios. Rabbits fed the DHA diet had highest total saturated fatty acids and lowest values of total ω-6 in both genders. DHA/ARA diet supported highest 20:4 (ARA), 22:6 (DHA) in both genders and least total saturated fatty acids in males. Effect of treatment of dietary lipid was not significant among different gender and ω-6/ω-3 ratios of the rabbits treated with FO, DHA and DHA/ARA were within the recommended range of 4. ALP activity was significantly lowest in fish oil group. Liver treated with DHA and DHA/ARA showed very mild inflammation, and those with sesame oil showed patchy moderate micro vesicular steatosis. The rabbit livers treated with soya bean oil and fish oil showed no significant abnormality. However, granuloma, hepatocellular necrosis or fibrosis was absent in all groups. In summary, evidence of pathological damage in the rabbit livers was very limited to mild patchy micro vesicular steatosis, mild patchy chronic inflammation and few scattered eosinophil. This study shows that long-term supplementation of dietary lipids especially fish oil has beneficial effect on the fatty acid profile, ALP activity and histopathology of liver of rabbits.
Keywords: Lipids; fatty acids; ω-6/ω-3 ratios; arachidonic acid; histology; fish oil